UPAYA MENINGKATKAN KEMAMPUAN MENULIS TEKS DESKRIPSI MENGGUNAKAN HURUF KAPITAL MELALUI MODEL PEMBELAJARAN KOOPERATIF TTW (THINK TALK WRITE): Penelitian Tindakan Kelas pada Kelas II Lower A SD Tumbuh 4 Yogyakarta Tahun Ajaran 2023 - Murdaningtyas, Annisa; Purwandari, Septiyati; Rahmawati, Puji; Ayudha Laksitaputri, Fransisca (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Good writing should adhere to proper rules and guidelines in the Indonesian language. This research aims to describe the implementation of the Think Talk Write (TTW) cooperative learning model that can enhance the use of capital letters in writing descriptive texts for Lower A grade students in the academic year 2023. The research method used is Classroom Action Research (CAR) with the Kurt Lewin research model design, conducted in two cycles. This research consists of four stages: planning, action, observation, and reflection. The results of the research indicate that the implementation of the TTW cooperative learning model is effective in improving students' ability to write descriptive texts using capital letters. This demonstrates that the cooperative approach can be an effective strategy in enhancing students' writing skills. It is recommended to continue implementing the TTW cooperative learning model in teaching writing descriptive texts and provide additional support for students who still need extra guidance in using capital letters. Furthermore, further research can be conducted to measure the long-term effects of implementing this learning model.